Análisis económico de derecho: el derecho a ser oído - Patroni Vizquerra, Ursula (2023)
The following article is aimed to expose how the discretionary manner in which the right to a hearing is regulated in the Peruvian national legislation regarding administrative penalty procedures does not reflect the requirements derived from its establishment in the Constitution and in several international treaties, and how, on the other hand, it generates a renounce to the efficiency brought by its exercise as a right, from the perspective of the economic analysis of law.